2018
DOI: 10.1080/02699052.2018.1429658
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of traumatic brain injury in Tehran, Iran

Abstract: The mechanism of TBI, the type of head injuries, and accompanying spine and abdominal injuries were significant prognostic factors in traumatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The most and least frequent CT-scan findings were EH (n = 24, 42.3%) and midline shift and intracerebral hemorrhage (n = 6, 10.8%), respectively. In Ahadi et al's study, concussion, diffuse brain injury (DAI), subarachnoid hemorrhage (SH), and EH occurred in 14 (0.4), 1 018 (26.7%), 551 (14.4), 787 (20.6), 1 018 (26.7%) participants, respectively (39). In Brown et al's study, SH, EH, and DAI rates were equal to 28%, 11%, and 2%, respectively (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most and least frequent CT-scan findings were EH (n = 24, 42.3%) and midline shift and intracerebral hemorrhage (n = 6, 10.8%), respectively. In Ahadi et al's study, concussion, diffuse brain injury (DAI), subarachnoid hemorrhage (SH), and EH occurred in 14 (0.4), 1 018 (26.7%), 551 (14.4), 787 (20.6), 1 018 (26.7%) participants, respectively (39). In Brown et al's study, SH, EH, and DAI rates were equal to 28%, 11%, and 2%, respectively (41).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the reported TBI incidence rate among American 0-4-year-old children and older adults was equal to 1 188 and 234 per 100 000 individuals, respectively (38). Ahadi et al reported in a study in Tehran, Iran, that the TBI incidence rates were 31.5% and 12.3% in the 21-30 and 41 -50 age groups, respectively (39). Due to the high TBI incidence rate, various complications, such as PTE, are caused (40).…”
Section: Discussionmentioning
confidence: 99%
“…It is an important contributing factor of morbidity and mortality in adult and pediatric population worldwide [1, 2]. Recently, substantial evidence confirms that the annual global incidence and prevalence rate of TBI increased progressively over the past years [3]. It seriously damages people's quality of life and results in a massive economic toll [4–6].…”
Section: Introductionmentioning
confidence: 99%